Analysis of COVID-related patents for antibodies and vaccines - Kausalya Santhanam (South Centre, 2023)
This paper provides an analysis of patents covering selected antibodies and vaccines used in the treatment or prevention of COVID-19. The aim of the report is to support national patent offices and interested parties in developing countries with information that can serve as guidance for the examination of the claims contained in relevant patents or patent applications. The antibody combination considered for the patent analysis in this paper are Casirivimab and Imdevimab. The vaccines considered for the patent analysis are mRNA-1273, Sputnik, ChAdOx1 nCoV-19 vaccine (AZD1222). The analysis was completed in May 2022.
Keywords: 300; Access to Medicines; Antibodies; COVID-19; Global Health; Health; Intellectual Property; Pandemic; Patent; Patent Examination; Patent Law; Patent Offices; Patent Policy; Patent Protection; Public Health; Vaccines